Adaptive coding of the value of social cues with oxytocin, an fMRI study in autism spectrum disorder. (March 2016) - Andari, Elissar; Richard, Nathalie; Leboyer, Marion; Sirigu, Angela
Abstract: The neuropeptide oxytocin (OT) is one of the major targets of research in neuroscience, with respect to social functioning. Oxytocin promotes social skills and improves the quality of face processing in individuals with social dysfunctions such as autism spectrum disorder (ASD). Although one of OT's key functions is to promote social behavior during dynamic social interactions, the neural correlates of this function remain unknown. Here, we combined acute intranasal OT (IN-OT) administration (24 IU) and fMRI with an interactive ball game and a face-matching task in individuals with ASD ( N  = 20). We found that IN-OT selectively enhanced the brain activity of early visual areas in response to faces as compared to non-social stimuli. OT inhalation modulated the BOLD activity of amygdala and hippocampus in a context-dependent manner. Interestingly, IN-OT intake enhanced the activity of mid-orbitofrontal cortex in response to a fair partner, and insula region in response to an unfair partner. These OT-induced neural responses were accompanied by behavioral improvements in terms of allocating appropriate feelings of trust toward different partners' profiles. Our findings suggest that OT impacts the brain activity of key areas implicated in attention and emotion regulation in an adaptive manner, based on the value of social cues.